Existence results for evolution equations with superlinear growth - Benedetti, Irene; Rocha, Eugénio M. (Topological Methods in Nonlinear Analysis, 2019)
By combining an approximation technique with the Leray-Schauder continuation principle, we prove global existence results for semilinear differential equations involving a dissipative linear operator, generating an extendable compact $C_0$-semigroup of contractions, and a Caratheodory nonlinearity $f\colon [0,T] × E → F$, with $E$ and $F$ two real Banach spaces such that $E \subseteq F$, besides imposing other conditions. The case $E eq F$ allows to treat, as an application, parabolic equations with continuous superlinear nonlinearities which satisfy a sign condition.